1966
DOI: 10.1515/zna-1966-0330
|View full text |Cite
|
Sign up to set email alerts
|

Erzeugung energiereicher Plasmen durch Lichtimpulse

Abstract: Light pulses from a Q-switched laser with a peak power of 250 MWatts and 3.5 joules are focussed on carbon and LiH targets in a vacuum chamber. Thereby a rapidly expanding plasma is formed. The expansion velocities of the electrons and ions are nearly equal. By means of an electric field the electrons are drawn out of the plasma; the ions are detected in a FARADAY box. From time of flight measurements particles with a maximum energy of 6.3 keV are found in the case of carbon and 1.7 keV in the case of LiH (ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is a consequence of the action of the space-charge field, which couples more strongly to the doubly charged ions. We note that such a charge segregation in expanding plasmas, where highly charged ions attain higher energies than low-charged ions, has already been found in very early experimental investigations on laser-induced plasmas [22,23] but continues until today to be a subject of intense experimental research [5,25,24].…”
Section: B Two Ion Charge Statesmentioning
confidence: 61%
“…This is a consequence of the action of the space-charge field, which couples more strongly to the doubly charged ions. We note that such a charge segregation in expanding plasmas, where highly charged ions attain higher energies than low-charged ions, has already been found in very early experimental investigations on laser-induced plasmas [22,23] but continues until today to be a subject of intense experimental research [5,25,24].…”
Section: B Two Ion Charge Statesmentioning
confidence: 61%
“…It has been observed that the primary plasma which is ejected from intensely irradiated targets by pulsed laser light may obtain velocities in the keV range (Lindor 1963, Isenor 1964, Opower and Press 1966. It was soon realized that these energies could potentially be utilized for a variety of purposes such as controlled thermonuclear fusion, space propulsion, generation of fracture, disintegration of materials, etc.…”
Section: The Primary Plasma In Pulsed Laser Radiationmentioning
confidence: 99%